Jasmonic acid regulates lignin deposition in poplar through JAZ5-MYB/NAC interaction - Zhao, Xin; Jiang, Xuemei; Li, Zeyu; Song, Qin; Xu, Changzhen; Luo, Keming (Frontiers in Plant Science, 2023)
Jasmonic acid (JA) is a phytohormone involved in plant defense, growth, and development, etc. However, the regulatory mechanisms underlying JA-mediated lignin deposition and secondary cell wall (SCW) formation remain poorly understood. In this study, we found that JA can inhibit lignin deposition and SCW thickening in poplar trees through exogenous MeJA treatment and observation of the phenotypes of a JA synthesis mutant, opdat1. Hence, we identified a JA signal inhibitor PtoJAZ5, belonging to the TIFY gene family, which is involved in the regulation of secondary vascular development of Populus tomentosa. RT-qPCR and GUS staining revealed that PtoJAZ5 was highly expressed in poplar stems, particularly in developing xylem. Overexpression of PtoJAZ5 inhibited SCW thickening and down-regulated the expression of SCW biosynthesis-related genes. Further biochemical analysis showed that PtoJAZ5 interacted with multiple SCW switches NAC/MYB transcription factors, including MYB3 and WND6A, through yeast two-hybrid and bimolecular fluorescent complementation experiments. Transcriptional activation assays demonstrated that MYB3-PtoJAZ5 and WND6A-PtoJAZ5 complexes regulated the expression of lignin synthetic genes. Our results suggest that PtoJAZ5 plays a negative role in JA-induced lignin deposition and SCW thickening in poplar and provide new insights into the molecular mechanisms underlying JA-mediated regulation of SCW formation.